SCIENTIFIC ARTICLE ON THE WAY TO SUSTAINABLE DEVELOPMENT: FEATURES OF THE TRANSITION OF DEVELOPED COUNTRIES TO A GREEN" ECONOMY - Мелиева Амаля Фарходжон кизи (Bright Mind Publishing, 2026)
The article is devoted to the analysis of the transition of developed countries to a "green" economy in the context of sustainable development tasks. The study is based on the statistical analysis of the Green Growth Index (GGGI) data, CO₂ emissions per capita, the share of renewable energy and the goals of the European Green Deal 2030. The dynamics of key indicators for 2018–2023, cross-country differences and the forecast for 2030 are considered. that the Nordic countries (Sweden and Denmark) are at the top of most sustainability indicators, while France, Germany and Austria are showing moderate but steady progress. The heterogeneity of the pace of decarbonization, the introduction of renewable energy sources and the development of "green" economic opportunities among developed countries was noted. The forecast for 2030 indicates a further decrease in emissions and an increase in the share of renewable energy, which confirms the effectiveness of the environmental strategies being implemented. The article provides a comprehensive view of the progress and challenges of the environmental transformation of developed countries, and also serves as a guideline for further research and development of sustainable development policies.
Keywords: Green economy, sustainable development, Green Growth Index, CO₂ emissions, renewable energy, European Green Deal, decarbonization, environmental transformation.